THE INFLUENCE OF NEW COMPOSITION OF MEAT PRODUCTS ON THEIR COMPETITIVENESS - Aleksandr Alekseevich Borisenko; Julia Vladimirivna Mityakina; Andrey Aleksandrovich Bratsikhin; Ludmila Aleksandrovna Saricheva; Aleksey Alekseevich Borisenko (Современная наука и инновации)
The article presents the complex method of an estimation of competitiveness of meat products. The method is adapted in accordance with the current state of consumer market of the country. The need to increased ecological purity of the composition (ecocomposition) food products in the evaluation of their marketing characteristics is justified. The results of the evaluation of competitiveness on the example of a new kind of meat products, the technology which is developed using natural ingredients and activated multicomponent brine were presented. It was demonstrated that the proposed technology can achieve significant competitive advantages